2021
DOI: 10.1016/j.ultsonch.2021.105499
|View full text |Cite
|
Sign up to set email alerts
|

High performance of ultrasonic-assisted synthesis of two spherical polymers for enantioselective catalysis

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 97 publications
1
2
0
Order By: Relevance
“…This indicated that ultrasound could renew the reaction surface through its ability to blow out the insoluble solid film layer on the surfaces of graphite particles. A similar phenomenon is commonly observed in processes involving ultrasound-assisted leaching [ [32] , [78] , [79] , [80] ].…”
Section: Resultssupporting
confidence: 70%
“…This indicated that ultrasound could renew the reaction surface through its ability to blow out the insoluble solid film layer on the surfaces of graphite particles. A similar phenomenon is commonly observed in processes involving ultrasound-assisted leaching [ [32] , [78] , [79] , [80] ].…”
Section: Resultssupporting
confidence: 70%
“…The XPS and EDX spectra of the non-US catalyst are shown in Figures 4 and 5, respectively. As reported in the literature [48], there are usually no substantial variations depending on the preparation method, hence the spectra of the non-US catalyst are only presented.…”
Section: The Measurements Of the Bet Surface Areamentioning
confidence: 99%
“…The development of innovative processes based on low-frequency and high-power ultrasound technology has grown in the last two decades due to its large versatility and application in several industrial sectors. Low-frequency ultrasound has been used to enhance from technological properties of polymers [ 1 , 2 ] to manufacturing processes of foods and beverages [ 3 , 4 , 5 ], alloys, and composite materials [ 6 , 7 ], in addition to its application in many research fields, such as tissue engineering [ 8 , 9 ], synthesis of chemicals [ 10 ], design of novel encapsulating systems [ 11 , 12 ], extraction of phytochemical compounds [ 13 ], and many others.…”
Section: Introductionmentioning
confidence: 99%